2022
DOI: 10.1038/s41586-022-05288-7
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear-embedded mitochondrial DNA sequences in 66,083 human genomes

Abstract: DNA transfer from cytoplasmic organelles to the cell nucleus is a legacy of the endosymbiotic event—the majority of nuclear-mitochondrial segments (NUMTs) are thought to be ancient, preceding human speciation1–3. Here we analyse whole-genome sequences from 66,083 people—including 12,509 people with cancer—and demonstrate the ongoing transfer of mitochondrial DNA into the nucleus, contributing to a complex NUMT landscape. More than 99% of individuals had at least one of 1,637 different NUMTs, with 1 in 8 indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
90
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(138 citation statements)
references
References 94 publications
9
90
0
1
Order By: Relevance
“…Thus, pathogen-induced cognitive alterations may benefit the reproductive capacity of neuronal viruses and other CNS pathogens. Indeed, neuronal cell mitochondria become compromised after the integration of the viral genome ( Wei et al, 2022 ). The resulting cognitive impairment benefits viral spread, as infected individuals exhibit behaviors that reduce host protection against infection ( Stefano et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, pathogen-induced cognitive alterations may benefit the reproductive capacity of neuronal viruses and other CNS pathogens. Indeed, neuronal cell mitochondria become compromised after the integration of the viral genome ( Wei et al, 2022 ). The resulting cognitive impairment benefits viral spread, as infected individuals exhibit behaviors that reduce host protection against infection ( Stefano et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Once the mitochondria have been infected, the virus may then have direct access to the nuclear genome. The intracellular transport of mitochondrial (mt)DNA as nuclear-mitochondrial segments (NUMTs) is an evolutionarily ancient phenomenon (Wei et al, 2022). Of interest, Wei et al (2022) analyzed whole-genome sequences from 66,083 individuals and found that this transfer process is ongoing and that 90% of these NUMTs underwent transfer Frontiers in Pharmacology frontiersin.org comparatively recently in evolutionary terms, i.e., after humans diverged from apes.…”
Section: Ancestral Factors Involved In Mitochondrial Alteration Cogni...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, although the present-day oDNA gene profile of an organism is shaped by many factors over its entire evolutionary history (including serial endosymbiosis events in the case of plastids (Keeling, 2010)), and not just its present-day situation (Janouškovec et al, 2017), some biological observations do at least qualitatively suggest that the compatibility of gene profiles of modern organisms and their environments does not conflict with our predictions (Figure 5). Recent work has shown that the transfer of mtDNA to the nucleus is ongoing in modern humans, estimating that one in every few thousand births experiences a de novo transfer of mtDNA material (Wei et al, 2022). It is known that transfer of ptDNA to the nucleus occurs frequently even over an individual plant’s lifetime (Stegemann et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These portions of DNA, called pseudogenes or nuclear-encoded mitochondrial sequences (NUMTs), are thought to be nonfunctional ( Puertas and González-Sánchez, 2020 ). The recent article by Wei et al (2022) published in Nature , reinforces the knowledge on NUMTs and their importance in the study of the mitochondrial genome. These pseudogenes make the study of mtDNA complex since any amplification of the mitochondrial genome may be accompanied by artifactual amplifications in parallel from nuclear pseudogenes.…”
mentioning
confidence: 59%